2005
DOI: 10.1111/j.1365-2141.2005.05799.x
|View full text |Cite
|
Sign up to set email alerts
|

Windy weather and low humidity are associated with an increased number of hospital admissions for acute pain and sickle cell disease in an urban environment with a maritime temperate climate

Abstract: Summary Sickle cell disease (SCD) is characterised by intermittent episodes of acute severe pain, related to vaso‐occlusion. Environmental factors are thought to play an important role, and studies in tropical countries have suggested that cold and rainy seasons are associated with increased episodes of acute pain. We have studied retrospectively the number of admissions with acute pain and SCD to King's College Hospital, London, together with daily meteorological records collected locally. Data from 1400 d an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 17 publications
6
63
5
1
Order By: Relevance
“…This finding was similar to previous reports from India [26,27]. However, the studies from other countries have shown temperature [28] or high wind speed and low humidity as precipitating factors for vaso-occlusive crisis in SCD subjects but not rainfall [29]. [33];other evidence has shown that healthrelated behaviours are strongly shaped by social factors, including income, education, and employment .…”
Section: Resultssupporting
confidence: 76%
“…This finding was similar to previous reports from India [26,27]. However, the studies from other countries have shown temperature [28] or high wind speed and low humidity as precipitating factors for vaso-occlusive crisis in SCD subjects but not rainfall [29]. [33];other evidence has shown that healthrelated behaviours are strongly shaped by social factors, including income, education, and employment .…”
Section: Resultssupporting
confidence: 76%
“…64 Increased episodes of acute pain are reported during the rainy season in regions with tropical climates, such as Jamaica 62 and Nigeria, 59 although no consistent effects of rain emerge where the climate is temperate, such as France 69 and England. 68 Again, the inconsistencies may be due to differences in housing and social factors.…”
Section: Climatic and Meteorologic Factorsmentioning
confidence: 99%
“…Some of the inconsistencies may also reflect the influence of location-specific features, including housing, clothing, and social and geographic factors, on the effects of temperature. 2 Although not usually noted by patients, wind speed has emerged as a factor that is consistently associated with pain in sickle cell disease, and higher wind speeds have been associated with increased hospital admissions for pain in England, 68 France, 69 Canada, 64 and the United States. 70 It is unclear how high wind speeds might precipitate episodes of acute pain, although there is evidence that skin cooling can provoke vaso-occlu- sion, 71 possibly as a result of impaired control of vascular tone.…”
Section: Climatic and Meteorologic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, the studies from other countries have shown rainy season, low temperature or high wind speed and low humidity as precipitating factors for vasoocclusive crisis in SCD subjects. [19][20][21][22] The mechanism of cold-induced painful crises is postulated to result from cold-induced diuresis, cold agglutinins, cryoglobulins or cutaneous vasoconstriction with shunting of blood to deeper vascular bed as per a study done in Jamaica. 3 The structure of the study did not allow independent confirmation of the perceived precipitating factors for pain, because no control observations were available.…”
Section: 10mentioning
confidence: 99%